Implementasi Bisnis Model Software as Services (SAAS) pada Sistem Rekam Medis Elektronik (Studi Kasus: klikmedika.id) - ,; ,; , (Seminar Nasional Informatika (SENATIKA), 2024)
Electronic Medical Records (EMR) have become a major issue and need in health service facilities (fasyankes). Data integration between health facilities and patient access needs is an important thing to do. Klik Medika is here as a solution to answer these challenges, but problems regarding compound data, data security and guaranteeing data integrity are issues that should be resolved. This research tries to provide an overview of the implementation of the Software as Service (SaaS) business model at Klik Medika. Testing whether implementing two-factor authentication to data encryption is enough to answer the challenges that arise. This system was built by combining a server-side programming framework and a client-side programming framework which has been proven to be able to create effective communication between users and the database